Menguak Akuntabilitas Kinerja Pemerintah Desa: Peran Kejelasan Anggaran, Pengendalian Akuntansi, dan Sistem Pelaporan - Fajrin, Farid (Universitas Islam Negeri Alauddin Makassar, 2024)
This study examines the impact of budget clarity, accounting control, and reporting systems on the accountability of village government performance, with regulatory compliance as a moderating variable. Using a quantitative approach with an associative research design, data were collected through questionnaires from 68 respondents in Libureng District, Bone Regency. The results indicate that budget clarity and accounting control have no significant effect on performance accountability, while the reporting system has a significant negative effect. Regulatory compliance moderates the impact of accounting control and reporting systems but does not moderate budget clarity. These findings highlight the crucial role of transparency and regulatory adherence in enhancing village government accountability.